Desalination plants and renewables combined to solve power and water issues. (15th October 2016) - Tsai, Yu-Ching; Chiu, Chih-Pin; Ko, Fu-Kuang; Chen, Tzong-Chyuan; Yang, Jing-Tang
Abstract: To enhance the security and dispatch ability of a system to supply water and electricity in a cost-effective manner, we propose a model to integrate the operations of a reservoir, hydroelectric power, desalination and wind power. The effect of seasonal energy storage for intermittent wind power is taken into account such that desalination plants can increase power consumption during cold seasons in which wind power is abundant but power demand is small, and can then relieve the burden of water supply from existing reservoirs to enable full operation during peak hours in hot seasons. Our model differs from the combination of an energy-storage system, pumped hydropower, desalination and renewables commonly applied in preceding research. A case study of Taichung city shows that the proposed model can fulfill that water requirement in 2030; the capability of sharing the peak load of existing hydroelectric power units is greatly increased from 398 MW to 1368 MW with an addition of extra 342-MW units, which also eliminate the requirement for 979-MW gas-turbine power fired with natural gas, even though, according to the proposed model, the greater expense from desalination can become compensated by the decreased expense from the power sector. Highlights: An integrated system among desalination and renewable energy has been studied. A case study of the water and power supply in Taichung city is evaluated. The seasonal mismatch among wind power, hydropower and power demand is alleviated. The net benefit is achieved by decreasing the installation of peak-power units.